This is because when we do verification of an
identity, we must work separately on both sides, and to see in the end
if we can get an equality. Because if we square both sides, that already means
that we assume that the equality exist in the beginning, so no need to
verify the identity.
Answer:
8xy + 65
Step-by-step explanation:
8(xy + 8) + 1.
8 x 8=
64 + 1=
65 (8xy + 65)
---------------------------------------------
LINE THE NUMBERS UP AND IT WILL MAKE SENSE
Answer:
yes
Step-by-step explanation:
The line intersects each parabola in one point, so is tangent to both.
__
For the first parabola, the point of intersection is ...
y^2 = 4(-y-1)
y^2 +4y +4 = 0
(y+2)^2 = 0
y = -2 . . . . . . . . one solution only
x = -(-2)-1 = 1
The point of intersection is (1, -2).
__
For the second parabola, the equation is the same, but with x and y interchanged:
x^2 = 4(-x-1)
(x +2)^2 = 0
x = -2, y = 1 . . . . . one point of intersection only
___
If the line is not parallel to the axis of symmetry, it is tangent if there is only one point of intersection. Here the line x+y+1=0 is tangent to both y^2=4x and x^2=4y.
_____
Another way to consider this is to look at the two parabolas as mirror images of each other across the line y=x. The given line is perpendicular to that line of reflection, so if it is tangent to one parabola, it is tangent to both.
Answer:
7672.50
Step-by-step explanation:
7500×0.23%=17.25
17.25×10=172.50
7500+172.50=7672.50
1.1 Factoring: 4x2+9y2+16z2-6xy-12yz-8xz
Thoughtfully split the expression at hand into groups, each group having two terms :
Group 1: -6xy-12yz
Group 2: 16z2-8xz
Group 3: 4x2+9y2
Pull out from each group separately :
Group 1: (x+2z) • (-6y)
Group 2: (x-2z) • (-8z)
Group 3: (4x2+9y2) • (1)
Looking for common sub-expressions :
Group 1: (x+2z) • (-6y)
Group 3: (4x2+9y2) • (1)
Group 2: (x-2z) • (-8z)